PENGEMBANGAN BAHAN AJAR BENTUK E-KOMIK DENGAN CANVA PADA MATA KULIAH MANAJEMEN PEMBELAJARAN - Manalu, Etty Octaviani; Purba, Rispah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Innovation in providing interesting teaching materials for students is deemed necessary, to maintain the quality of learning and also foster student activity in reading and understanding lecture material so that the learning process runs well and provides good final results for these students. The aim of this research is to develop e-comic teaching materials for learning management courses. The method used in this research is the research and development method and the ADDIE model (Analysis, Design Development, Implementation and Evaluation). The results of this research show that the development of e-comic teaching material products received very feasible criteria from the assessment results of 3 validators and the responses of 23 students. According to material experts, the average percentage is 86.67%; according to media experts, it is very feasible with a percentage of 93.33%; according to linguists it was 93.33% and the results of the student questionnaire percentage were 92.00%. Based on these results, it can be concluded that the e-comic teaching material product developed is suitable for use as teaching material.